Pengaruh Budaya Terhadap Keputusan Membeli Produk Mie Instant Indomie - Denny Asmas; Ahmad Tarmizi (J-MAS (Jurnal Manajemen dan Sains), 2019)
Indomie Instant Noodle is one of the products of instant noodles favored by consumers because it produces a variety of variations that are in the form of fried noodles (ordinary fried noodles, special fried foods, noodles club taste roasted chicken, jumbo fried noodles) and in the form of Mie Kuah (flavored chicken broth, chicken curry flavor, onion chicken flavor, special chicken flavor, Soto Ayam flavor). Indomie instant noodle products that are made in a variety of variations are tailored to the tastes of consumers who are also varied, which are always changing as the environment changes, also according to the consumer behavior itself. Therefore, every production of instant noodle Indomie always produce various products that are varied and adjusted to the condition of the region. This research aims to analyse the influence of cultural variables on the decision to purchase Indomie instant noodle products. The results of this study showed that there was a significant influence of the cultural variables on Indomie instant noodle product purchasing decision.